2017
DOI: 10.21873/invivo.11030
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Samples for the Diagnosis of Pemphigus vulgaris Using the BIOCHIP Approach: a Pilot Study

Abstract: Abstract. Pemphigus vulgaris (PV) isPemphigus vulgaris (PV) is a rare autoimmune intraepithelial blistering skin disease characterized by the presence of circulating autoantibodies directed against desmoglein 3 (DSG3) and desmoglein 1 (DSG1), resulting in loss of the normal epithelial cell-to-cell adhesion, through a process called acantholysis (1). The diagnosis of PV is generally based on clinical features, histology and immunological tests, notably direct and indirect immunofluorescence and enzyme linked im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The study of De et al perfectly reproduced this finding and the authors perfectly agreed with the explanation concerning higher Dsg1 levels in severe disease [106]. In contrast to the previously discussed research, one Italian study was designed to assess the use of a BIOCHIP approach compared with ELISA in PV [107]. In fact, the authors considered saliva an unsuitable substrate for autoantibody detection because of the discordance between techniques found when using saliva samples.…”
Section: Blistering Diseasessupporting
confidence: 55%
“…The study of De et al perfectly reproduced this finding and the authors perfectly agreed with the explanation concerning higher Dsg1 levels in severe disease [106]. In contrast to the previously discussed research, one Italian study was designed to assess the use of a BIOCHIP approach compared with ELISA in PV [107]. In fact, the authors considered saliva an unsuitable substrate for autoantibody detection because of the discordance between techniques found when using saliva samples.…”
Section: Blistering Diseasessupporting
confidence: 55%
“…in their study used the serum and salivary samples to detect anti-Dsg autoantibodies for diagnosis of pemphigus and concluded that saliva is not a suitable sample for BIOCHIP. [ 8 ] Gornowicz-Porowska et al . from Poland compared the original BIOCHIP method with modified BIOCHIP method using monoclonal IgG instead of routine IgG and concluded that modified BIOCHIP has as higher sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the previous studies, the current study also revealed that Dsg 3 and BP 180 were the commonly detected antigens using BIOCHIP in pemphigus and pemphigoid groups, respectively [ Table 3 ]. [ 1 4 5 6 8 9 10 11 12 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other samples, collection of saliva is convenient, non-invasive, economical and not influenced by the menstrual cycle. For this reason, some studies have focused on using saliva to detect diseases and have showed some clinical benefits [10,11]. Similarly, saliva could be used to improve the comprehensiveness of studies on TCM constitution.…”
Section: Introductionmentioning
confidence: 99%